Nonapeptide Receptor Distributions in Promising Avian Models for the Neuroecology of Flocking - Naomi R. Ondrasek (Frontiers in Neuroscience, 2018)
Collective behaviors, including flocking and group vocalizing, are readily observable across a diversity of free-living avian populations, yet we know little about how neural and ecological factors interactively regulate these behaviors. Because of their involvement in mediating a variety of social behaviors, including avian flocking, nonapeptides are likely mediators of collective behaviors. To advance the neuroecological study of collective behaviors in birds, we sought to map the neuroanatomical distributions of nonapeptide receptors in three promising avian models that are found across a diversity of environments and widely ranging ecological conditions: European starlings, house sparrows, and rock doves. We performed receptor autoradiography using the commercially available nonapeptide receptor radioligands, 125I-ornithine vasotocin analog and 125I-linear vasopressin antagonist, on brain tissue sections from wild-caught individuals from each species. Because there is known pharmacological cross-reactivity between nonapeptide receptor subtypes, we also performed a novel, competitive-binding experiment to examine the composition of receptor populations. We detected binding in numerous regions throughout the brains of each species, with several similarities and differences worth noting. Specifically, we report that all three species exhibit binding in the lateral septum, a key brain area known to regulate avian flocking. In addition, sparrows and starlings show dense binding in the dorsal arcopallium, an area that has received scant attention in the study of social grouping. Furthermore, our competitive binding results suggest that receptor populations in sparrows and starlings differ in the lateral septum versus the dorsal arcopallium. By providing the first comprehensive maps of nonapeptide receptors in European starlings, house sparrows, and rock doves, our work supports the future use of these species as avian models for neuroecological studies of collective behaviors in wild birds.